Impact of PCV13 on community-acquired pneumonia by C-reactive protein and procalcitonin levels in children. Issue 37 (5th September 2017) - ,; Hau, Isabelle; Craiu, Irina; Gillet, Yves; Gras-Le Guen, Christèle; Launay, Elise; Morin, Laurence; Lorrot, Mathie; Martinot, Alain; Varon, Emmanuelle; Béchet, Stéphane; Angoulvant, François; et al.
Highlights: One of the largest cohorts (n = 9586) of children with community-acquired pneumonia. First CAP study reported the effectiveness of PCV13 according to CRP and PCT levels. After PCV13, marked reduction of CAP with levels of CRP ≥ 100 mg/L and/or PCT ≥ 4 ng/mL. No PCV13 impact observed on CAP with low CRP/PCT levels. Abstract: Background: Many countries have observed an early and strong impact of implementation of the 13-valent pneumococcal conjugate vaccine (PCV13) on community-acquired pneumonia (CAP). High levels of C-reactive protein (CRP) and procalcitonin (PCT) are considered biomarkers of bacterial infection (particularly infection due to pneumococcus); therefore, PCV13 implementation should have different effectiveness on CAP depending on the levels of these two biomarkers. To demonstrate this assumption, we analyzed the evolution of number of CAP cases seen in pediatric emergency departments in France after PCV13 implementation (in 2010) by levels of these two biomarkers. Methods: From June 2009 to May 2015, 8 pediatric emergency units prospectively enrolled all children (1 month to 15 years) with radiologically confirmed CAP. Results: A cohort of 9586 children with CAP was enrolled (median age 3 years). CAP with pleural effusion (PE-CAP) and proven pneumococcal pneumonia (PP-CAP) accounted for 5.5% and 2.0% of cases. During the study period, the number of cases of overall CAP decreased by 25.4%, hospitalized CAP by 30.5%, PE-CAP by 63.4%, CAP with CRP level ≥ 100 mg/L by 50.9%, CAP with PCT level ≥ 4 ng/L by 60.4% and PP-CAP by 86.4%. We found no change in number of cases of CAP with low levels of CRP (<20 or <40 mg/L) or PCT (<0.5 ng/mL). The number of cases of CAP overall increased (20.0%) in the last year of the study as compared with the preceeding year but not cases with CRP level ≥ 100 mg/L and/or PCT level ≥ 4 ng/mL. Conclusion: PCV13 implementation has had a strong impact on number of CAP cases with high levels of CRP and/or PCT in children but no impact on that with low levels of these two biomarkers. Five years after PCV13 implementation, a sustained reduction in CAP cases is observed.